Prognostic Prediction of Cardiopulmonary Exercise Test Parameters in Heart Failure Patients with Atrial Fibrillation - Valentim Gonçalves, A (2020)
Background: Atrial fibrillation (AF) is associated with increased mortality in heart failure (HF) patients. Objective: To evaluate whether the risk of AF patients can be precisely stratified by relation with cardiopulmonary exercise test (CPET) cut-offs for heart transplantation (HT) selection. Methods: Prospective evaluation of 274 consecutive HF patients with left ventricular ejection fraction ≤ 40%. The primary endpoint was a composite of cardiac death or urgent HT in 1-year follow-up. The primary endpoint was analysed by several CPET parameters for the highest area under the curve and for positive (PPV) and negative predictive value (NPV) in AF and sinus rhythm (SR) patients to detect if the current cut-offs for HT selection can precisely stratify the AF group. Statistical differences with a p-value <0.05 were considered significant. Results: There were 51 patients in the AF group and 223 in the SR group. The primary outcome was higher in the AF group (17.6% vs 8.1%, p = 0.038). The cut-off value of pVO2 for HT selection showed a PPV of 100% and an NPV of 95.5% for the primary outcome in the AF group, with a PPV of 38.5% and an NPV of 94.3% in the SR group. The cut-off value of VE/VCO2 slope showed lower values of PPV (33.3%) and similar NPV (92.3%) to pVO2 results in the AF group. Conclusion: Despite the fact that AF carries a worse prognosis for HF patients, the current cut-off of pVO2 for HT selection can precisely stratify this high-risk group.